2014
DOI: 10.1089/ct.2014;26.273-276
|View full text |Cite
|
Sign up to set email alerts
|

Cold Climate Is a Risk Factor for Thyroid Cancer

Abstract: Background The incidence rates of differentiated thyroid cancers of all sizes increased between 1988 and 2005 in both men and women. Exposure to ionizing radiation is the best-established environmental risk factor for thyroid cancer. Nonionizing radiation from cell phones has also been implicated. A positive correlation between all-cancer incidence rates and latitude and an inverse correlation between all-cancer incidence rates and temperature have been reported. In the present study, we examined the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In addition, exposures to certain environmental conditions have also been reported to have carcinogenic effects on the thyroid gland. For example, physical factors, such as ionizing radiation exposure 11 ; geographic factors, such as living in a volcanic environment 12 ; and a cold climate 14 have been reported to be risk factors for thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exposures to certain environmental conditions have also been reported to have carcinogenic effects on the thyroid gland. For example, physical factors, such as ionizing radiation exposure 11 ; geographic factors, such as living in a volcanic environment 12 ; and a cold climate 14 have been reported to be risk factors for thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier findings also support the higher risk of thyroid cancer for those populations who live in a cold environment. 32 In a cold environment, our body needs high thermogenesis to maintain body temperature. Thyroid hormones play a vital role in thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, there have been a few reports that either support or negate these recent findings. 3234 These contradicting findings may be a result of the influence of disparities in many demographic factors such as lifestyle, socio-culture, diet, education, smoking and alcohol consumption along with age, gender, race/ethnicity, and genetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ambient temperature, which changes depending on longitude, latitude, altitude, and even day and night, can contribute to the risk of cancer mortality [ 2 ]. Recent studies have shown that a low-temperature environment may be a major risk factor for several types of cancer, such as lung, bladder, ovarian, skin, stomach, breast, thyroid, and prostate cancer, by increasing their incidence and mortality rates [ 3 , 4 , 5 , 6 ]. However, there is little known about the mechanisms responsible for the effects of low ambient temperature on human diseases, especially malignant tumors.…”
Section: Introductionmentioning
confidence: 99%